Gender, Medicine and Globalisation: The Case of Women Ayurveda Physicians of Kerala, India. (January 2020) - Abraham, Leena
Abstract: Women's entry into the exclusively male-dominated field of Ayurveda in large numbers and their pursuit of a professional career as physicians, observed since the 1980s in India, are socially and historically significant events. Their overwhelming participation marks a rupture in the unchallenged control of the field by men of certain castes and families of medical lineages for centuries. In Kerala, interestingly, this has occurred when women's overall workforce participation has remained low. This article attempts to analyse women's work in Ayurveda in Kerala and its consequences for Ayurvedic transformations in the state that are simultaneously aimed at consolidation of a regional identity and expansion of its global market. It analyses the experiences of women practitioners in the context of the local gender power dynamics and negotiations that define and direct their professional participation. How do these women Ayurveda practitioners negotiate forces of professionalisation as well as gender marginalisation? What are the various personal and societal resources that they mobilise to succeed as Ayurveda practitioners? Do their subjectivities, negotiations and resources alter practices of Ayurveda and infuse it with different sensibilities? Based on interviews of women Ayurveda practitioners from diverse caste, religious and economic backgrounds, the paper argues that women's experiences vary according to their social locations and all women are not empowered or dis-empowered in a similar fashion by the same gender system. While globalisation has led to increased opportunities for women physicians, their careers and contributions continue to be restricted by the specific gender structures and ideologies that govern women's lives in the respective local and global sites.